Transport And Mental Sciences In Raqqa During The Abbasid Era (132-380 )Hijri 750-993 AD - عباس رندة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study of the Euphrates Island region is one of the most interesting studies, as it is an important geographical location that has an impact and importance in Arab-Islamic history, where it constitutes the first line of defense for the homes of Islam, and the meeting point of Arab-Islamic civilizations, so the interest began to study its cities in detail in Various political, economic and scientific aspects, to show the importance of these cities and what they have provided in various historical periods. This study aims to highlight the development of science in the city of Raqqa during the Abbasid era, in which the scientific movement witnessed a great boom, such as the spread of educational centers and the emergence of many scientists and historians who contributed to the development of science a lesson, teaching and writing, through which all kinds of science flourished. Religious and linguistic, as well as the mental sciences, were evident through the many works of these sciences, which had a positive impact on the flourishing of the compositional movement during the Abbasid period. The study dealt with a geographical and historical overview of the city of Raqqa, which dealt with the Islamic location and conquest of the city and its role in the Umayyad era, as well as the situation of the city in the Abbasid era, as well as the study explained the factors that made it play a major intellectual and scientific role in the construction of Arab-Islamic civilization And the study of science that has emerged at the hands of famous scientists.